The effects of COVID-19 in global warming through the application of data science - Rafia, Tasnim; Mahmood Hasan, Tanveer; Hassan, Raini (Kulliyyah of Information and Communication Technology International Islamic University Malaysia, 2022)
Abstract— Global warming is a constant alarming concern. Simultaneously, temperature escalation throughout the world, too in Asia, has turned into dismay which is indicating unexpected natural disasters and inconvenience. Covid-19 has added a new disruption to conventional viability. As a consequence of temporary confinement, a perceptible change in places might be noted in electricity as well as motor vehicle usage before and after the Covid-19 pandemic. This research is inspired by Sustainable Development Goals 7 and 13 which is Affordable and clean energy and the Climate Action to investigate the scale of climate change in several Asian regions before and after the Covid-19 pandemic. The focal point is concerning two contrasted states of global warming whether Covid-19 has any influence in this regard. Some contemporary temperature datasets, Nitrogen Dioxide emission datasets, that incorporate years (2016 to 2021), have been analysed, using machine learning algorithms in order to accomplish the assertion. According to the analysis, the average temperature has come down from 25.5°C(in 2019) to around 24°C(in 2021) along with a detectable change in carbon as well as nitrogen emission. Therefore, the pandemic is supposed to be positively correlated to global warming. For future work, a further investigation might be conducted concerning situations of the possible smallest region in alongside a dataset with a much-improved algorithm in order to resolve the examination more productively.